Konsep Kafaah Keluarga Kiai Ditinjau dari Perspektif Fikih Madzhab: (Studi Kasus Pondok Pesantren Raudlatul Ulum 2 Putukrejo Gondanglegi) - Hasbulloh Huda, Muhammad; Indah Nastiti, Soni (JURNAL PUSAKA, 2023)
This research is conducted by the fact that Islamic boarding schools as institutions that produce good generations require that boarding school caregivers also look for qualified cadres of relatives. Islam recommends kafaah as a basic criterion in choosing a partner in order to achieve household goals. On average, kiai families marry their sons to fellow kiai children too, the reason for taking the view of kiai families in PP. Raudlatul Ulum 2 Putukrejo, whether the views of the kiai families there are different or the same. Regarding the formulation of the problem, namely what is the concept of kafaah in building a household and what is the concept of kafaah for the family of kiai. Raudlatul Ulum 2 Putukrejo when viewed from a family sociology perspective. The results of this research are that the concept of kafaah in building a household is the religious factor that is the number one factor in kafaah. Religion includes good morals. Apart from religion, there are lineage factors. The concept of kafaah when viewed from a family sociology perspective is in accordance with the theory of homogamy and heterogamy. This is due to choosing because there are similarities, but there is also the opposite, choosing because there are differences (not necessarily equal). Key words: kafaah; household; family studies; Islam; marriage